E-Commerce, Literasi Keuangan, Pengetahuan Kewirausahaan, dan Minat Berwirausaha Mahasiswa Akuntansi - Adi Arta, I Kadek; Sujana, I Ketut (E-Jurnal Akuntansi; Vol 34 No 3 (2024), 2024)
Entrepreneurship will bring profits if each individual is able to develop and provide new innovations for the sustainability of their business. The aim of this research is to obtain empirical evidence regarding the influence of e-commerce, financial literacy, and entrepreneurial knowledge on accounting students' entrepreneurial interest. This research was conducted at the Undergraduate Accounting Study Program, Faculty of Economics and Business, Udayana University, with a total sample of 84 respondents who were students from the class of 2019 & 2020 who had taken the Entrepreneurship course. Sampling used a probability sampling method with proportionate stratified random sampling using a questionnaire as a data collection method. The data analysis technique used is multiple linear regression analysis. The results of the analysis show that e-commerce, financial literacy, and entrepreneurial knowledge have a positive effect on accounting students' entrepreneurial interest. The higher the level of e-commerce, financial literacy and entrepreneurial knowledge an individual has, the greater the interest in entrepreneurship among accounting students. Keywords: E-Commerce; Financial Literacy; Enterpreneurship Knowledge; Entrepreneurial Interest.